(untitled) (Gaceta Técnica, 2019)
In this research the behavior of a real scale experimental joint (column-beam joint) formed by three reinforced concrete elements, 1 column and 2 beams, attached to a structural steel column in the upper level is studied. The object in question was subjected to the action of cyclic loads in a single direction, in a pseudostatic test for 5000 s, in order to observe which element of the concrete cylinders failed and which the failure mode was. A mathematical model was created in the ABAQUS CAE software, in order to verify that the design of the gasket of the test piece complied with the normative requirements for the design of base plates, based on concrete crushing and thickness of the base plate. In the bolts its resistance to shear forces, tensile deformation, and verification by tensile cone in the concrete and tensile stress within the cracked area was verified, and it was obtained as a result that the failure was produced by cracking of the reinforced concrete